A diffused community tuberculosis outbreak that could be detected earlier using surveillance data, Japan, 2012–2014 - Masaki Ota (International Journal of Mycobacteriology, 2021)
Background: Early detection of an outbreak is a role of disease surveillance systems; however, tuberculosis (TB) surveillance systems were underutilized to detect the outbreaks. In mid-2015, a local health office of central Japan noticed the number of TB cases of city in 2012–2014 were well above the expected numbers. This study was conducted to determine whether and when a community TB outbreak could be detected and characterize the cases using the national surveillance data. Method: The surveillance data of the A city and surrounding areas were retrospectively reviewed and analyzed for 2006–2018. Results: The TB notification rates of the A city from 2012 to 2014 were 28.0 (95% confidence interval [CI]: 20.3–38.4), 26.0 (95%CI: 18.6–36.0), 28.2 (95%CI: 20.3–38.4) per 100,000 population, respectively, higher than that of the entire prefecture (13.6, 13.0, 13.3, respectively). Similarly, in the neighboring B city, the rates of 2012 and 2014 were 51.0 (95%CI: 27.2–87.2) and 51.2 (95%CI: 27.3–87.5), respectively, higher than that of its parent prefecture (13.4 and 12.7, respectively). By the end of July 2012 (A city) or August 2012 (B city), the accumulated numbers of TB cases exceeded the previous annual TB cases. The average TB notification rates of A and B cities for 2012–2014 were higher than the surrounding areas. Conclusion: A community TB outbreak without well-defined setting could be detected by monitoring TB surveillance data.